PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN HARGA TERHADAP KEPUASAN KONSUMEN JAYA FRIED CHICKEN (JFC) DI SELURUH OUTLET CABANG SINGARAJA - Parmayasa, Gede; Kusuma, Gusti Putu Eka (Komunitas Manajemen Kompetitif, 2023)
This study aims to determine the effect of product quality, service quality, and price on consumer satisfaction. This type of research is quantitative research because it involves numbers and statistical calculation techniques. The population of this research is all consumers who have consumed Jaya Fried Chicken (JFC) Outlet Singaraja branch. The sampling technique was carried out using the Non Probability Sampling method with purposive sampling and accidental sampling. The number of samples in study obtained as many as 108 samples. Sources of data used in this study are primary data in the form of questionnaires measured by the Linkert scale and secondary data in the form of books, journals, theses, and other documents. The data analysis technique used in this study is multiple linear regression analysis with the help of SPSS version 20 program. The results of this study indicate that (1) product quality has a positive and significant effect on customer satisfaction, (2) service quality has a positive and significant effect on customer satisfaction. and (3) price has a positive and significant effect on consumer satisfaction.